Local Wisdom of Relativity as Living Law in Personal Data Protection: Reconstruction of Islamic Law Ethics against Intimate Digital Crimes in Indonesia - Ismed Batubara; Rini Novita; Dhani DS Hasibuan; Hengky Syahyunan; Indra Fajar (International Journal of Law, Crime and Justice, 2026)
This study aims to examine the influence of local wisdom as a living law on personal data protection behavior, as well as assess the role of Islamic law ethics and digital literacy in the context of intimate digital crime in Indonesia. The background of this research is based on the increasing cases of misuse of personal data in the digital space that have not been fully responded to effectively through formal legal approaches. The method used a quantitative approach with a correlational explanatory design. Data were obtained through the distribution of a questionnaire based on the Likert scale to 150 respondents who were selected purposively, then analyzed using descriptive statistics, Pearson correlation, and simple linear regression. The results showed that local wisdom of alwasliyahan had a positive and significant influence on personal data protection behavior (β = 0.42; p < 0.05). Islamic legal ethics serve as a mediating variable that strengthens the relationship, while digital literacy provides a positive influence at a moderate level. These findings show that the internalization religious and cultural values plays an important role in shaping individual awareness and behavior in protecting personal data in the digital era. The conclusion of this study emphasizes that local wisdom can function effectively as a living law in supporting the protection of personal data. This research makes theoretical contribution the development of the study of Islamic law and the sociology of law, as well as practical implications for policy formulation that integrates formal regulations, cultural values, and digital literacy.